Visualization and networking analysis of processing seafood towards future trends: A bibliometric analysis from 2010 to 2024 - Baarimah, Abdullah O.; Mokaizh, Aiman A.; Alazaiza, Motasem Y. D.; Al-Zghoul, Tharaa (Elsevier B.V., 2024)
Seafood waste presents a significant environmental and economic challenge due to its high organic content and substantial volume. This bibliometric study aims to comprehensively map the research landscape of seafood waste valorization by analyzing 1,109 publications from the Scopus database between 2010 and 2024. The findings indicate a dramatic increase in research output, particularly in the last five years, with over 35 % of studies published during this period, reflecting a heightened global interest in sustainable treatment methods for seafood waste. China emerges as the leading contributor, with 722 articles and 29,433 citations, followed by Japan and various European countries. The predominant discipline is identified as "Agricultural and Biological Sciences," accounting for 42 % of the studies, while "Food Chemistry" is the most prolific journal, contributing 46 publications and 1,690 citations. The analysis highlights key extraction techniques, including supercritical fluid extraction (SFE), ultrasound-assisted extraction (UAE), and membrane separation, with SFE achieving extraction yields of up to 12 %. Notable bioactive compounds derived from seafood waste include omega-3 fatty acids, collagen, and chitosan, which have applications in pharmaceuticals, nutraceuticals, and cosmetics. The study underscores critical challenges, such as the need for cost-effective and scalable extraction methods to enhance the recovery of these valuable compounds. Additionally, innovative strategies, including hybrid extraction techniques and encapsulation, are emphasized as vital for improving the stability and bioavailability of bioactive components. The findings also reveal a disparity between publication volume and citation impact, highlighting influential authors who have made significant contributions despite fewer publications. This study points to emerging research opportunities focused on optimizing extraction processes and advancing sustainable practices, ultimately aiming to transform seafood waste into valuable resources that benefit both the economy and the environment.